Virgil's Homeric Lens. - Dekel, Edan (Routledge monographs in classical studies., 2011)
Virgil's Homeric Lens reevaluates the traditional view of the Aeneid's relationship to Homer's Iliad and Odyssey. Almost since the death of Virgil, there has been an assumption that the Aeneid breaks into two discrete halves: Virgil's Odyssey, and Virgil's Iliad. Although modified in various ways over the centuries, this neat dichotomy has generally diminished the complexity and resonance of the connection between the two canonical epic poets. This work offers an alternate approach in which Virgil uses the transformative power of the Odyssey as a precise filter through which to read the Iliadi.